Where Has the Rum Gone? Firms' Choice of Transport Mode under the Threat of Maritime Piracy - Alexander-Nikolai Sandkamp; Shuyao Yang (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Despite a general agreement that piracy poses a significant threat to maritime shipping, empirical evidence regarding its economic consequences remains scarce. This paper takes a step towards filling the gap by combining firm-level Chinese customs data with information on pirate attacks to investigate how exporting firms respond to maritime piracy. It finds that overall exports along a particular shipping route fall following an increase in pirate activity. In addition, piracy induces firms to switch from ocean to air shipping, while the remaining ocean shipments become larger.
Keywords: F14; F19; N70; R41; 330; Trade; transport; China; piracy